Problemas
Write the equation that models the function described. Shift the parent function, y=log_(2)x up three units and left 4 units. y=3+log_(2)(x+4) y=-4+log_(2)(x+3) y=4+log_(2)(x-3) -4+log_(2)(x-3) y=-3+log_(2)(x+4) y=4+log_(2)(x+3) y=3+log_(2)(x-4) y=-3+log_(2)(x-4)
Roztwór
Pedro
maestro · Tutor durante 5 años
4.1
(300 Votos)
Respuesta
The equation that models the function described is \(y=\log_{2}(x+4)+3\).
Explicación
## Step 1The problem involves shifting the parent function
up by three units and left by four units. This is a transformation of the parent function.## Step 2The transformation of a function can be represented by the equation \(y=f(x-h)+k\), where
represents the horizontal shift and
represents the vertical shift.## Step 3In this case, the function is shifted up by three units, which means
. The function is also shifted left by four units, which means
.## Step 4Substituting
and
into the equation, we get \(y=\log_{2}(x+4)+3\).